2009
DOI: 10.1007/s11295-009-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth performance and fecundity of Eucalyptus camaldulensis and E. tereticornis during domestication in southern India

Abstract: Bulk seedlots of two unpedigreed multiprovenance seed production areas (SPAs) each of Eucalyptus camaldulensis and Eucalyptus tereticornis and one pedigreed seedling seed orchard (SSO) of E. tereticornis were planted in genetic gain trials at three southern Indian trial sites. At the time of seed collection, fewer than 30% trees flowered in these orchards, except in one E. camaldulensis SPA where 73% of the trees flowered, which had an estimated outcrossing rate of 86%. The E. tereticornis SSO was dominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…This is supported by findings in previous E. macarthurii (Swain et al 1999) and E. nitens genetic gain trials (Jones, pers. comm 1 ) in South Africa and in E. camaldulensis genetic gain trials in India (Varghese et al 2009), where bulks of the same nominal level of improvement did not differ significantly from each other.…”
Section: Gainsmentioning
confidence: 90%
“…This is supported by findings in previous E. macarthurii (Swain et al 1999) and E. nitens genetic gain trials (Jones, pers. comm 1 ) in South Africa and in E. camaldulensis genetic gain trials in India (Varghese et al 2009), where bulks of the same nominal level of improvement did not differ significantly from each other.…”
Section: Gainsmentioning
confidence: 90%
“…Reports on controlled inter-specific hybrid eucalypts production and their importance in genetic improvement were available since 1960 in India for the commercially important species like Eucalyptus camaldulensis , Eucalyptus tereticornis and Eucalyptus grandis (Venkatesh and Kedharnath 1965; Venkatesh and Sharma 1977, 1979). However, eucalypts breeding program in India mainly focused on improvement of pure species (Varghese et al 2009) which is obviously a prerequisite for hybrid development. Many earlier hybrid selections in Congo and Brazil were from sporadic hybrids identified from open pollinated seed orchards and later shifted to planned attempts for production of inter-specific hybrids (Potts and Dungey 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, in relation to the flower intensity or abundance, Butcher et al (2009) found little flowering in the populations of E. camaldulensis in the arid regions of Australia, whereas Varghese et al (2009) found inter-species differences in the fertile trees and fecundity percentages in the south of India. Mora et al (2007) found that the Cowell provenance exhibited an early flowering that was higher than other populations from Australia.…”
Section: Resultsmentioning
confidence: 94%